Baiat dan Perilaku Beragama - Hamzah Khaeriyah (LPPM IAIN Sorong, 2017)
The linkage between the allegiance and religious behavior is always proportional. This is always played by the founders of religious sects, so there is a feeling of belonging and responsibility to comply with, so that no wonder then that many people who feel free, when entering a new religious sect, if it must go through allegiance. Because many cases that result in a system that is ugly, as LDII who later became a serious threat of State, which was later labeled a banned terrorist organization, DI/TII, chairman Raden Mas Kartosuwiryo, which then intends to establish an Islamic state, and Baitul Arqam in Malaysia. All that, departing from the pledge of allegiance, yet in the context of Ahmadiyah adherents do not worry about the other so will its links with politics. Moreover, the Ahmadiyya no official decision stating that Ahmadis are prohibited from being an activist and a political party for violating the rules will be penalized, the most severe was fired from Ahmadiyah organization or removed from the stewardship of Ahmadiyah. They argue that Islam is destroyed because of political problems.